English medical lexicography: diachronic analysis - Gordiyenko, O. V.; Гордієнко, Олена В'ячеславівна (My University, 2020)
The article is devoted to the medical lexicography diachronic analysis in the context of historical development of English medical terminology. The research covers the period from 13 century to 2020 year. The corpus comprises 487 medical dictionaries (only first issue) of different types collected from the catalogues of National Library of Medicine, Simon Frazer University Library, The British Library, The Internet Archive, Library of Congress, WorldCat, National Ukrainian Library named after V.I. Vernadskyi. The methodology used has a complex character and combines historical and etymological approach, comparative analysis and method of dictionary criticism. The study covered the observation of linguistic and extralinguistic factors. Among linguistic we distinguished the history of medical term, history of English, development of general and medical lexicography with its theoretical and practical features. As extralinguistic – the history of medicine and history in general taking into consideration the events specific for medical reference books (dictionaries) creation. The juxtaposition of the results suggested such periodisation of medical lexicography in general and English medical lexicography (EML) in particular. The achieved results helped to divide EML into two periods: pre-lexicographic (XIII c. – XVI c.) and lexicographic (XVII c. – 2020). The lexicographic period (XVII c. – 2020) consists of developing (XVII c. – XVIII c.) (internationalization of medical terminology and terminography, the need for translation dictionaries, the birth of EML) and developed (XIX c. – 2020) (the development of EML, the creation of practical and theoretical instruments in EML ). The developed period was subdivided into 3 parts: 1. 19 c. – 1918 year; 2. 1919 – 1945 years; 3. 1946 – 2020 years. The results showed that English medical lexicography is a complex system developing in the context of global scientific and technical progress with its distinct features of each period in EML and helped to come to conclusion that EML has its rich history, but still needs the solution of some theoretical and practical issues for fruitful professional communication in medicine. Статтю присвячено діахронічному аналізу медичної лексикографії в контексті історичного розвитку англійської медичної термінології та лексикографії. Дослідження охоплює період з 12 століття до 2020 року. Корпус містить 487 медичних словників різних типів, зібраних із каталогів National Library of Medicine, Simon Frazer University Library, The British Library, The Internet Archive, Library of Congress, WorldCat, Національної бібліотеки України імені В.І. Вернадського. Методологія роботи має комплексний характер і поєднує в собі історичний та етимологічний підхід, порівняльний аналіз і метод словникової критики. Дослідження охоплювало вивчення лінгвістичних та екстралінгвістичних факторів. Серед лінгвістичних було виділено історію медичного терміну, історію англійської мови, розвиток загальної та медичної лексикографії з її теоретичними та практичними особливостями. Що стосується екстралінгвістичних – історія медицини та історія з урахуванням подій, характерних для створення медичних довідників (словників). Зіставлення отриманих результатів дозволило розробити періодизацію медичної лексикографії загалом та англійської медичної лексикографії (дала – АМЛ) зокрема. Досягнуті результати допомогли поділити АМЛ на два періоди: долексикографічний (XIII c. – XVI ст.) та лексикографічний (XVII ст. – 2020 р.). Лексикографічний період (XVII ст. – 2020 р.) складається із розвиваючого (XVII ст. – XVIII ст.) (інтернаціоналізація медичної термінології та термінографії, необхідність перекладацьких словників, народження АМЛ) та розвинутого (XIX ст. – 2020 р.) (розвиток АМЛ, створення практичних і теоретичних інструментів в АМЛ). Розвинутий період було поділено на субперіоди: 1) 19 c. – 1918 рік; 2) 1919 – 1945 роки; 3) 1946 – 2020 роки. Результати показали, що англомовна медична лексикографія є комплексною системою, яка розвивається в контексті глобального науково-технічного прогресу. Було виділено відмінні риси кожного періоду АМЛ, які продемонстрували, що АМЛ має свою багаторічну історію, але все ж потребує вирішення деяких теоретичних і практичних питань для плідної професійної комунікації в медицині.
Keywords: medical lexicography; English medical terminology; medical dictionary; periodisation; extralinguistic and linguistic factors; медична лексикографія; англомовна медична термінологія; медичний словник; періодизація; екстралінгвістичні та лінгвістичні фактори